ESTIMASI BIAYA GARANSI DENGAN PENDEKATAN SKALA WAKTU TERBAIK PRODUK KENDARAAN TRUK MERK "X" DI PT ABC - Puspita, Hermita Dyah; Norina, Rida; Puspawardhani, Gianti (Inaque : Journal of Industrial and Quality Engineering, 2023)
ABSTRACT A warranty is an agreement between a manufacturer and a consumer that guarantees the quality of a product for a certain period or period of use. There is a warranty, products that are defective before the warranty period expires will be replaced or repaired by the manufacturer. From the consumer's perspective, a warranty serves as a guarantee of protection against a product failing or not performing as expected and also as a provider of information about the quality of the product. From the manufacturer's perspective, warranties provide benefits by protecting the manufacturer from excessive consumer complaints. This study aims to determine the estimated warranty costs for “X” brand truck products sold by PT ABC using the best time scale method. The policy implemented by the company is a two-way warranty policy, specifically a warranty policy for automobile products for a period of 3 years or 100,000 km, whichever comes first. The purpose of this study is to perform estimates for branded heavy goods vehicles. The estimated parameters of the truck damage model were obtained using the maximum likelihood method. With the Golden Section algorithm, the resulting parameter is ∈0 = 0.35125 with a minimum variance coefficient obtained of 0.7427391 and a guarantee limit at L= 5.4588. The K distribution of the best fitting time scale is an exponential distribution with parameter λ = 0.964902. The estimated warranty cost for truck brand “X” in company “ABC” using the best time scale method produces a cost of IDR 958,949,134. Keywords: 1 Dimension Guarantee, Best Time Scale, Maksimum Likelihood Estimation.